Empowering Vocabulary Mastery through Digital Game-based Learning: A Pathway to Enhance Reading Comprehension - Atika Zami Fauzia; Yuyun Yulia (Journal of Education Technology, 2025)
The low level of students’ vocabulary mastery, which affects reading comprehension, needs to be addressed through the implementation of appropriate instructional strategies. The increasing use of digital games in education indicates a growing demand for more interactive learning techniques to enhance vocabulary retention and language proficiency. This study aims to explore the impact of Digital Game-Based Learning using Bamboozle on students’ vocabulary mastery in relation to their reading comprehension. The Digital Game-Based Learning strategy was implemented in an experimental class using a quantitative pre-experimental design. The participants of this study were 34 eleventh-grade students. Data were collected through vocabulary tests and reading comprehension tests administered at the pretest and posttest stages. Data analysis was conducted using descriptive and inferential statistics, specifically the Wilcoxon Signed-Rank test. The results indicate a significant improvement in students’ posttest scores, with an average gain of 24.26 points. The Wilcoxon Signed-Rank test revealed a statistically significant improvement (p < 0.001), and the effect size (r = 0.807) indicates a strong impact of the intervention. These findings demonstrate that Digital Game-Based Learning through Bamboozle effectively enhances students’ vocabulary mastery, which directly contributes to improved reading comprehension. Therefore, it can be concluded that the implementation of Bamboozle-based Digital Game-Based Learning is an effective instructional strategy for improving students’ vocabulary mastery and reading comprehension.